Acute toxicity of cassava residues in Hyphossobrycon eques Steindachner (1982) - ALONSO, Paulo Arthur de Jesus (2023)
Detoxification of Cassava is a fundamental process for processing the roots into by-products, but this process occurs stocking roots in water. However, its toxicity released into aquatic environment still is unknown. For this reason, this study evaluated the acute toxicity of effluent with cassava root residue on the fish Hyphossobrycon eques. Therefore, sensitivity tests were performed with five concentrations of KCl (0.4; 0.9; 1.4; 1.9; and 2.4 g.L-1) and acute toxicity test (LC50-96h) with eight effluent concentrations with cassava root residue (0; 3.8; 4.7; 5.7; 6.6; 7.6; 8.5 and 9.5 mg.L-1), and four replicates. During the toxicity test, behavioral changes and mortality rate were observed. The estimated sensitivity for H. eques was 1.12 g.L-1, and the lethal concentration at 50% (LC50-96h) of the effluent with cassava root residue was 6.2 mg.L-1, classified as moderately toxic xenobiotic. During the experimental period, 100% mortality was observed at the highest concentration (9.5 mg.L-1) and behavioral changes such as agitation, erratic swimming and increased opercular beating of fish exposed to the xenobiotic. Therefore, the effluent with cassava root residue is a risk to the aquatic environment, causing changes in the behavior and mortality of H. eques.